The Accord on Fire and Building Safety in Bangladesh: A New Paradigm for Limiting Buyers' Liability in Global Supply Chains? - Jaakko Salminen (OXFORD UNIV PRESS INC, 2022)
The Accord on Fire and Building Safety in Bangladesh (the Accord) is generally seen as a positive development in ensuring that Bangladeshi garment industry workers have access to safe working conditions. A central structural difference between the Accord and earlier corporate social responsibility (CSR) initiatives is that the Accord takes the form of an enforceable contract that directly connects first-world buyers with representatives of the third-world laborers of their supply chains. Traditionally, CSR mechanisms tread a fine line between a promise of decent labor conditions, often targeted at first-world consumers, and the nonbinding nature of such mechanisms, at least from the perspective of third-world laborers. The chief competitor of the Accord, the Alliance for Bangladesh Worker Safety (the Alliance), follows the traditional model. Thus the Accord represents a break from earlier nonbinding and worker-exclusive CSR by providing a new paradigm stressing enforceability and inclusivity. The novel structural aspects of the Accord are viewed positively by scholarship, interest groups, and general reporting. My starting point is this distinction between the positive, empowering image attributed to the enforceable agreement in the case of the Accord and the negative, hollow-words image of compliance mechanisms that do not take the form of an enforceable agreement, such as the Alliance. I argue that the possibilities for controlling liability allowed by an enforceable governance agreement can outweigh the possibilities for controlling liability allowed by reliance on strict conceptions of privity. From this perspective, the Accord can be critiqued as the herald of a new CSR paradigm that allows buyers new methods for controlling liability over their global supply chains. Additionally, the new paradigm comes with a whitewashing effect towards consumers and regulators. I argue that even more pronounced, however, can be its whitewashing effect towards adjudicators. Courts and arbitral tribunals may be prone to value the sanctity of the four-corners private ordering of transnational contracts, such as the Accord, over locally embedded legal safeguards.